Intake of Fiber and Sodium Toward the Risk of Obesity in Primary School Children in the City of Padang Indonesia - Azrimaidaliza, A; Ramdika, Sari Bema; Helmizar, H (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
High food intake and unhealthy diet are one of the main factors of obesity. The aim of the study was to determine the association between fiber and sodium intake with the risk of obesity occurrence among elementary school children in the Andalas Public Health Centre, Padang City. This study used a case control design with location was on Elementary School No. 30 and Kartika 1-10. The amount of sample was 114 students (57 cases and 57 controls). Fiber and sodium intake was calculated by Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and child obesity was based on weighing and then compared to age. The result showed that the mean of fiber intake among case (deviation, standard) was 16,89 g (more and less 9,46 g) while the mean of fiber intake among control was 17,4 g (more and less 33,66 g). Then, the mean of sodium intake among case was 1.624,53 mg (more and less 367,34 mg) while the mean of sodium intake among control was 1.353,48 mg (more and less 350,58 mg). The result also showed that there was not statistically significant fiber intake with the risk of obesity among elementary school children (p-value=0,677; OR=1,19). However, higher sodium intake has proved statistically will increase the risk of obesity 2,29 times among elementary school children than normal sodium intake. Multivariate analysis showed that fat intake is a confounding factor of the relationship between fiber and sodium intake with the risk of obesity. Based on the result, the school side should monitor food and beverages that on sale in the canteen and around school, also giving education to school children how to choose a healthy and nutritious food.ABSTRAKPola makan yang kurang sehat merupakan salah satu faktor utama terjadinya obesitas. Penelitian ini bertujuan untuk mengetahui hubungan antara asupan serat dan natrium dengan risiko kejadian obesitas pada anak sekolah dasar di wilayah kerja Puskesmas Andalas Kota Padang. Penelitian ini menggunakan desain case control dengan lokasi penelitian di SDN 30 dan SD Kartika 1-10. Jumlah responden penelitian sebanyak 114 orang (57 kasus dan 57 kontrol). Asupan serat dan natrium anak dinilai melalui Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) dan status obesitas anak ditentukan berdasarkan hasil penimbangan kemudian dibandingkan dengan umur. Hasil analisis diketahui rata-rata asupan serat kasus (standar deviasi), yaitu 16,89 g (lebih kurang 9,46 g) sedangkan rata-rata asupan serat kontrol, yaitu 17,4 g (lebih kurang 33,66 g) kemudian rata-rata asupan natrium kasus sebesar 1.624,53 mg (lebih kurang 367,34 mg) sedangkan rata-rata asupan natrium kontrol sebesar 1.353,48 mg (lebih kurang 350,58 mg). Hasil penelitian juga menunjukkan tidak ada hubungan yang bermakna antara asupan serat dengan risiko kejadian obesitas pada anak sekolah dasar (p-value=0,677; OR=1,19) sebaliknya asupan natrium yang lebih secara statistik terbukti meningkatkan risiko kejadian obesitas sebesar 2,29 kali pada anak sekolah dasar dibandingkan asupan natrium yang cukup. Hasil analisis multivariat diketahui asupan lemak merupakan variabel confounding terhadap hubungan asupan serat dan asupan natrium terhadap risiko obesitas pada anak sekolah. Berdasarkan hal tersebut kepada pihak sekolah sebaiknya melakukan pengawasan terhadap jajanan yang dijual di kantin dan lingkungan sekitar sekolah serta memberikan edukasi kepada anak melalui kurikulum mengenai memilih makanan jajanan yang sehat dan bergizi.